2022
DOI: 10.32604/cmes.2022.016224
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Water Pollution Causes and Control Countermeasures in Liaohe Estuary via Support Vector Machine Particle Swarm Optimization under Deep Learning

Abstract: This study explores the loss or degradation of the ecosystem and its service function in the Liaohe estuary coastal zone due to the deterioration of water quality. A prediction system based on support vector machine (SVM)-particle swarm optimization (PSO) (SVM-PSO) algorithm is proposed under the background of deep learning. SVM-PSO algorithm is employed to analyze the pollution status of the Liaohe estuary, so is the difference in water pollution of different sea consuming types. Based on the analysis results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…All three models have shown good performance in predicting WQI, effectively shortening the calculation time and reducing errors in the derivation process of sub-indicators. Guize Liu et al [149] proposed a prediction system based on the Support Vector Machine and Particle Swarm Optimization algorithm. The results show that the maximum error of the water pollution index prediction model for sample prediction is 2.41%, the average error is 1.24%, and the root mean square error is 5.36 × 10 −4 , with a correlation coefficient of 0.91 squared.…”
Section: Prediction Of Coastal Water Quality Index Using Machine Lear...mentioning
confidence: 99%
“…All three models have shown good performance in predicting WQI, effectively shortening the calculation time and reducing errors in the derivation process of sub-indicators. Guize Liu et al [149] proposed a prediction system based on the Support Vector Machine and Particle Swarm Optimization algorithm. The results show that the maximum error of the water pollution index prediction model for sample prediction is 2.41%, the average error is 1.24%, and the root mean square error is 5.36 × 10 −4 , with a correlation coefficient of 0.91 squared.…”
Section: Prediction Of Coastal Water Quality Index Using Machine Lear...mentioning
confidence: 99%
“…Human activities affect groundwater quality [ 14 ]. Due to the imperfect sewage treatment facilities, wastewater would pollute the surrounding surface water systems and soil [ 15 , 16 ]. The discharge of domestic wastewater and the excessive use of chemical fertilizers aggravate the pollution of groundwater.…”
Section: Related Workmentioning
confidence: 99%
“…The results showed that, for predicting electrical conductivity (EC) and total hardness (TH) in the test stage, ANFIS-DE was the most appropriate model. Liu et al (2022) used support vector machine particle swarm optimization with deep learning to investigate the causes of water pollution and control countermeasures in the Liaohe estuary. The results showed that the SVM-PSO approach has excellent predictive performance.…”
Section: Introductionmentioning
confidence: 99%